1998
DOI: 10.1056/nejm199811263392202
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand Factor–Cleaving Protease in Thrombotic Thrombocytopenic Purpura and the Hemolytic–Uremic Syndrome

Abstract: Nonfamilial thrombotic thrombocytopenic purpura is due to an inhibitor of von Willebrand factor-cleaving protease, whereas the familial form seems to be caused by a constitutional deficiency of the protease. Patients with the hemolyticuremic syndrome do not have a deficiency of von Willebrand factor-cleaving protease or a defect in von Willebrand factor that leads to its resistance to protease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
1,325
5
43

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,606 publications
(1,416 citation statements)
references
References 21 publications
27
1,325
5
43
Order By: Relevance
“…Mutations in the ADAMTS13 gene were shown to cause congenital TTP [6], whereas IgG autoantibodies inhibit the enzyme in most cases of the acquired form of the disease [7][8]. The standard treatment of acquired idiopathic TTP consists of plasma exchange with fresh frozen plasma [9][10], thereby removing large VWF multimers as well as autoantibodies to ADAMTS13 and replacing the enzyme [11][12].…”
Section: Word Countsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the ADAMTS13 gene were shown to cause congenital TTP [6], whereas IgG autoantibodies inhibit the enzyme in most cases of the acquired form of the disease [7][8]. The standard treatment of acquired idiopathic TTP consists of plasma exchange with fresh frozen plasma [9][10], thereby removing large VWF multimers as well as autoantibodies to ADAMTS13 and replacing the enzyme [11][12].…”
Section: Word Countsmentioning
confidence: 99%
“…Tsai et al [3] and Furlan et al [4] independently identified a VWF-cleaving protease (ADAMTS13) missing from the plasma of patients with congenital TTP [5] and severely deficient in patients with acquired idiopathic TTP. Mutations in the ADAMTS13 gene were shown to cause congenital TTP [6], whereas IgG autoantibodies inhibit the enzyme in most cases of the acquired form of the disease [7][8]." To avoid repetitions we left this part of the introduction as it was.…”
mentioning
confidence: 99%
“…Endothelial cell dysfunction and subsequent release of high amount of von Willebrand factor could be an important step in the sequence of events leading to intravascular platelet aggregation in TTP. Recently, additional ®ndings shed light on the pathophysiology of TTP [2,3]. Indeed, a de®ciency in von Willebrand factor-cleaving protease activity has been reported in TTP, whereas in hemolytic uremic syndrome (HUS), this enzyme activity was found normal [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, additional ®ndings shed light on the pathophysiology of TTP [2,3]. Indeed, a de®ciency in von Willebrand factor-cleaving protease activity has been reported in TTP, whereas in hemolytic uremic syndrome (HUS), this enzyme activity was found normal [2,3]. These ®ndings may account for the e cacy of plasma therapy, i.e., plasma infusion (PI) or plasma exchange (PE), in the treatment of TTP since it could restore missing plasma components.…”
Section: Introductionmentioning
confidence: 99%
“…A severely deficient ADAMTS13 activity correlates with increased amounts of highly active, high molecular weight multimers (HMWM) of VWF that cause a thrombotic microangiopathy, which is commonly referred to as thrombotic thrombocytopenic purpura (TTP) (9)(10)(11). TTP is caused either by mutations of the ADAMTS13 gene or by acquired autoantibodies that inhibit ADAMTS13 activity (12).…”
Section: Introductionmentioning
confidence: 99%